Dukungan Keluarga terhadap Wanita dengan Kanker Serviks Stadium IIIB yang Mendapat Concurrent Chemoradiation Therapy (CCRT): Studi Kasus - Ningsih, Dini Cristia; Fitriana, Nazula; Effendy, Christantie (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2025)
Background: Patients with cervical cancer undergoing CCRT therapy often experience a decline in quality of life such as physical complaints, decreased spiritual well-being, and poor mental health. Family support plays a crucial role for individuals with certain illnesses, including those with cervical cancer.Objective: To describe family support for woman with stage IIIB cervical cancer undergoing CCRT.Case report: Mrs. Y, 37 years old, had been married for 10 years with a parity status of P2A1. She was currently a housewife in a middle-class family. The patient came for a routine check-up at the ICC Oncology Clinic of Dr. Sardjito General Hospital with a diagnosis of stage IIIB cervical cancer, scheduled for CCRT, and anemia. She has undergone chemotherapy twice and radiation therapy 10 times. Additionally, she had no history of hypertension, diabetes mellitus, or previous cancer.Outcomes: CCRT therapy had several physical and psychological impacts on the patient. These were including diarrhea, weight loss, oral problems, frequent fatigue, tingling in the hands and feet, the menstrual cycle alteration, bleeding, anxiety, and sexual relationships modification. Throughout the treatment process, the patient had received strong family support in the form of informational, emotional, instrumental, and appreciation support.Conclusion: Family support enhances self-confidence, provides motivation, and offers significant encouragement to patients. Therefore, family support plays a crucial role in the treatment of cervical cancer, especially for patients undergoing CCRT therapy.INTISARILatar belakang: Pasien kanker serviks yang mendapat terapi CCRT sering dilaporkan mengalami penurunan kualitas hidup yang berkaitan dengan keluhan fisik, penurunan kesejahteraan spiritual, dan kesehatan mental yang buruk. Dukungan keluarga memiliki peranan penting pada individu dengan penyakit tertentu, termasuk individu dengan kanker serviks.Tujuan: Mengetahui gambaran dukungan keluarga pada wanita yang menderita kanker serviks stadium IIIB dengan CCRT.Laporan kasus: Ny. Y, berusia 37 tahun, sudah menikah selama 10 tahun dengan status paritas P2A1. Pekerjaan pasien saat ini sebagai ibu rumah tangga dan pasien termasuk keluarga kelas menengah. Pasien datang untuk melakukan kontrol rutin di Poliklinik Onkologi ICC RSUP Dr. Sardjito dengan diagnosis kanker serviks stadium IIIB pro CCRT dengan anemia. Pasien sudah menjalani kemoterapi sebanyak dua kali dan radiasi sebanyak 10 kali. Selain itu, pasien tidak memiliki riwayat penyakit hipertensi, DM,  dan kanker sebelumnya.Hasil: Terapi CCRT memberikan beberapa dampak bagi pasien, baik secara psikis maupun psikologis. Dampak yang dialami pasien seperti diare, berat badan turun, masalah pada mulut, sering merasa lelah, kesemutan pada tangan dan kaki, perubahan siklus menstruasi, perdarahan, perasaan cemas dan perubahan dalam hubungan seksual. Selama menjalani pengobatan, dukungan keluarga yang didapatkan pasien baik dukungan informasional, penghargaan, instrumental maupun emosional sudah baik.Simpulan: Dukungan keluarga meningkatkan rasa percaya diri, memberikan motivasi dan semangat yang besar bagi pasien sehingga dukungan keluarga mempunyai peranan penting dalam proses pengobatan kanker serviks terutama pasien dengan terapi CCRT.